ANALISIS SOSIAL EKONOMI MASYARAKAT DESA HUTAN PASCA KEGIATAN HPH PT. SIAK RAYA TIMBER DI KABUPATEN PELALAWAN, PROVINSI RIAU. - Ruslan Hamidy; Zulkarnaini Zulkarnaini; Zulfan Saam (Program Pascasarjana Universitas Riau, 2011)
This study aims to assess the socio-economic development of a rural community,especially guided village (the village nonbinaan ratio), aspects considered include income,education, length of stay at the study site, distance to the socio-economic infrastructure(markets, health centers, etc.. ), ownership of land. Identifying the factors that influencecommunity development programs and analyze around HPH PT. Siak Raya Timber. Prospectsexpected future community development programs around the forest should always payattention to those aspects of internal and external of a community forest itself. Someprograms must be developed and given priority are: strengthening and enabling/empoweringinstitutional formal/informal, improving infrastructure, improving participatory programsthrough cooperation among relevant agencies or government policy